362 IS THERE A NEUROBEHAVIORAL PROFILE ASSOCIATED WITH IN UTERO EXPOSURE TO SOLVENT ABUSE?. Issue 1 (1st January 2007) - Singal, M.; Prasad, A. N.; Kamaya-Miyakawa, V.; Benoit, T.; Hanlon-Dearman, A.; Prasad, C.
Abstract : Background: Alcohol and solvent abuse are common in certain populations in Manitoba. Infants born to mothers with significant alcohol and/or solvent exposures are difficult to distinguish on the basis of dysmorphic features alone. Our experience at the Clinic for Alcohol and Drug Exposed Children (CADEC) led us to believe that solvent-exposed children may have a distinct neurobehavioral profile that has hitherto gone unrecognized in comparison with alcohol-exposed children. Objective: To identify differences in neurobehavioural profile following alcohol and/or solvent exposure using standardized psychometric tools. Methods: A prospective blinded design: 26 children (2-6 years) attending the CADEC underwent a neurologic examination and assessments for adaptive behavior (Vineland Adaptive Behavioural Scales [VABS]) and emotional and social functioning (Achenbach Child Behavioral Checklist [CBCL]). Results: Twenty-six children were assessed, 18 with alcohol + multiple exposures and 8 with exposure purely to solvents. Conclusions: Solvent-exposed children were less affected in motor and daily living skills in comparison with the alcohol and multiple-exposures group in a blinded assessment using VABS. However, both groups performed significantly lower than the standardized norms expected for their age. The solvent-exposed group showed more severe manifestations in several behavioral subdomains (emotion, withdrawn, internalizing behavior, and pervasive development) of the CBCL in comparison with alcohol-exposed children. Given their particular difficulties in communication and socialization on the VABS and propensity to internalize emotions, the solvent-exposed group may be at a great risk of secondary disabilities and psychiatric comorbid disorders and are deserving of funding support and early intervention.